The Development of Teaching Supplement "When Vape Means Fire" for Respiratory System Disorders Learning at SMA Negeri 1 Bumiayu - Yusdike Adystia; Lisdiana Lisdiana; Ari Yuniastuti (International Conference on Science, Education, and Technology, 2022)
The development of the teaching supplement "When Vape Means Fire" is a solution in complementing the teaching materials used by teachers in learning respiratory system disorders where the teaching supplement developed provides actual information and it is also based on research results about vaping and its dangers. This study aims to develop a teaching supplement "When Vape Means Fire" and measure its feasibility. The research method in this research is Research and Development with ADDIE model development design (Analysis, Design, Development, Implementation, and Evaluation). The data collection technique used a questionnaire with an instrument in the form of a feasibility test sheet for teachers and students. The data is then analyzed quantitatively to determine the feasibility category and further deepened by qualitative analysis. The results of the development of the "When Vape Means Fire" teaching supplement were tested for feasibility. The feasibility was tested on 2 biology teachers at SMA Negeri 1 Bumiayu with 97.5% results and 30 students in class XI MIPA 5 at SMA Negeri 1 Bumiayu with 87.3% results, both of which were in the Very Feasible category.